Efeitos das isoflavonas da soja associadas à vibração mecânica de baixa intensidade no tecido ósseo de ratas osteopênicas - Florencio-Silva, Rinaldo [UNIFESP] (2011)
Introduction: It has been shown that both soy isoflavones (ISO) and low intensity high frequency mechanical vibration (VIB) have protective effects in bone tissue of ovariectomized (OVX) rats. Objective: We investigated whether combined treatments with ISO and VIB would exhibit cooperative effects in bone tissue of OVX rats. Methods: Fifty female Wistar rats at the age of 6 months were either sham-operated or OVX. After operation, the rats were divided in five groups: SHAM; OVX; OVX treated daily by gavage with 200mg/kg/body weight of ISO for 90 days (OVX-ISO); OVX treated with VIB, 20 min./day, at 60 Hz, 0.5g, 5 days/ week for 90 days (OVX-VIB) and OVX treated with ISO and VIB (OVX-ISO+VIB). After treatment, the femurs and tibias were collected and its length and thickness were measured. The femurs were then processed for histomorphometry, histochemistry and biochemical assay. The tibias were frozen for subsequent physical and mechanical tests. Results: Treatments did not have significant effects on body weight and in the bone measurements, except in the tibial thickness of the OVX-ISO and OVX-ISO+VIB groups that was significant higher than the SHAM group. Physical tests showed that the immersed weight, content of organic material and bone density were higher in the SHAM, OVX-VIB and OVX-ISO+VIB groups than the other groups, while the bone volume, bone mineral density, mineral material and the ash weight were higher in the OVX and OVX-ISO groups than the other groups and there were no significant differences in the mechanical tests among the groups. Treatment did not have significant effects in the trabecular bone volume, but it was not detected cortical bone loss in the group treated with the combined therapy. The treatments showed positive effects in the content of glycosaminoglycans, as well as in the organization of collagen fibers and these effects was higher in the OVX-ISO+VIB group. The TUNEL-positive cell profile was similar among the groups. Conclusion: These results demonstrate that the combined treatment (ISO+VIB) have better effects in the bone tissue constituents of ovariectomized osteopenic rats, when compared with the treatments isolated.